28 Prevalence and prognosis of lynch syndrome and sporadic mismatch repair deficiency in the combined PORTEC-1, -2 and -3 endometrial cancer trials. (13th November 2020) - Post, C; Stelloo, E; Smit, V; Ruano, D; Tops, CM; Vermij, L; Rutten, TA; Jürgenliemk-Schulz, IM; Lutgens, LC; Jobsen, JJ; Nout, RA; Crosbie, EJ; et al.
Abstract : Introduction: Here we aimed to evaluate the prevalence and prognosis of Lynch Syndrome (LS)-associated endometrial cancer (EC) in relation to sporadic mismatch repair deficient EC (MMRd-EC) in the combined PORTEC-1, -2 and 3 trials comprising 1336 ECs. Methods: MMR-status was determined by MMR-immunohistochemistry (MLH1/PMS2/MSH6/MSH2). MMRd-ECs with detected promoter hypermethylation of MLH1 were classified as sporadic (methylated MMRd-EC). For unmethylated MMRd-EC cases tumor and normal tissue next-generation sequencing was performed. ECs with MMR germline mutations were classified as LS-associated (LS MMRd-EC). Unmethylated MMRd-ECs without MMR germline mutations were classified as MMRd-EC due to other causes (other MMRd-EC). Overall and recurrence-free survival were estimated and compared using Kaplan-Meier method and pairwise log-rank test. Results: Among the 1336 ECs, 926 were MMR proficient. Of the 410 MMRd-EC, 376 could be fully triaged; 281 (75%) were methylated MMRd-ECs; 37 (10%) LS MMRd-ECs, and 58 (15%) other MMRd-ECs. The overall LS prevalence was 2.8%. Overall 5-year survival for LS MMRd-EC was 89% (95%CI 79–100%; p=0.055), other MMRd-EC 96% (92–100%; p=0.001), both compared to methylated MMRd-EC 79% (74–84%); 5-year recurrence-free survival was 92% (84–100%; p=0.123), 95% (89–100%; p=0.002), compared to 79% (74–84%), respectively. Conclusion: The prevalence of LS in the PORTEC EC trial population was 3% and within the MMRd group 10%. LS MMRd-EC seems to have a better overall and recurrence-free survival than sporadic MMRd-EC caused by hypermethylation. Further research into the underlying causes of non-hypermethylated somatic MMRd-EC is ongoing.